Investigation of the key factors influencing the urban building code violations in Mashhad, Northeastern Iran (2002–2022) - Bikdeli, Sona (City, territory and architecture, 2025)
A building code violation is recognized as each difference from building regulations and codes, which can occur during the development and implementation of urban constructions. This subject is one of the major concerns of urban growth in Iranian cities, such as Mashhad city. Hence, the main research objective is to investigate the key factors, influencing the urban building code violations in Mashhad city for two temporal intervals of 2002 and 2022. For this purpose, a multi-criteria method was assumed to estimate the correlations between four major types of building code violations, gathered from annual official data of Mashhad Municipality, and some urban configurations, such as the spatial distribution of population, land price, and main land uses, extracted from statistical data and satellite imageries. Based on the GIS analysis, results revealed that a significant volume of total building violations (> 88% in 2002 and > 78% in 2022) belongs to illegal occupation or changes of the urban lands and fields in most districts, i.e., “code #2: illegal land use changes” and “code #3: illegal occupation of fields”. Overall, the key factors influencing the building violations were categorized as urban population (positive effect) and urban land price (negative effect). Besides, the main sensitive violation was identified as code #3, correlated with all independent variables (i.e., urban population, land price, and main land use) in Mashhad City from 2002 to 2022. The research also revealed that the reasons in the back of building violations in Mashhad city, dominantly are financial revenue for low-income residents instead of the spatial motives.